Mechanism of arable land ecological security impact on arable land quality in different geomorphological areas of Northeast China - Pang, Ranran; Qian, Fengkui; Li, Wenbo (Scientific reports, 2025)
Assessing the arable land ecological security ( ALES ) and its quality is not only crucial for ensuring food security but also serves as an essential foundation for achieving sustainable agricultural development. This study focuses on three representative geomorphological areas in Northeast China as research subjects. It employs the bivariate spatial autocorrelation method to explore the spatial correlation between ALES and arable land quality, and uses spatial regression models to investigate the specific impact of ALES on arable land quality. The results show varying degrees of correlation between ALES and arable land quality in different geomorphological areas, and arable land quality changes with variations in ALES . To enhance arable land quality, the western low hilly area should prioritize improving the level of agricultural mechanization, while the central plain area and eastern mountain area mainly rely on the role of the net primary productivity index. When the net primary productivity index increases by 1 gC/m 2 ·a, arable land quality in the areas increases by 190.41 and 196.68, respectively. This study pioneers a geomorphological heterogeneity perspective to develop targeted arable land protection strategies based on regional resource advantages and key ecological constraints affecting arable land quality improvement. The findings provide a scientific foundation for local governments to formulate food security policies and promote sustainable agricultural development.